A novel adenylyl cyclase type 5 inhibitor that reduces myocardial infarct size even when administered after coronary artery reperfusion. (August 2018) - Zhang, Jie; Levy, Daniel; Oydanich, Marko; Bravo, Claudio A.; Yoon, Seonghun; Vatner, Dorothy E.; Vatner, Stephen F.
Abstract: We developed a novel adenylyl cyclase type 5 (AC5) inhibitor, C90, that reduces myocardial infarct size even when administered after coronary reperfusion. This is key, since it is not practical to administer a drug to a patient with myocardial infarction before revascularization, and is one reason why so many prior drugs, which reduced infarct in experimental animals, failed in clinical trials. C90 is the most potent AC5 inhibitor, as exhibited by its IC50 value for AC5 inhibition, which was 5 times lower than the next most potent AC5 inhibitor. C90 reduced cAMP in response to forskolin in wild type mice by 42%, but no longer reduced cAMP in response to forskolin in mice with disruption of AC5, indicating that the mechanism of C90 was specific for AC5 inhibition. Compared with vehicle treatment, C90 reduced infarct size by 64% at a dose of 0.6 mg/kg. Thus, C90 is a novel, selective and potent AC5 inhibitor that reduces infarct size, when delivered after coronary artery reperfusion, rendering it potentially clinically useful. It also reduces beta-adrenergic receptor signaling, which will provide additional benefit to patients with coronary artery disease or heart failure. Highlights: C90 is a novel, selective and potent AC5 inhibitor. C90 delivered after coronary reperfusion reduces infarction, important clinically. C90 reduces beta receptor signaling, an additional benefit to cardiac patients.